THE RELATIONSHIP BETWEEN GENIALLY LEARNING MEDIA AND THE MATHEMATICAL CREATIVE THINKING ABILITY OF FIFTH GRADE ELEMENTARY SCHOOL STUDENTS - Aritonang, Shanty Margareta; Maksum, Arifin; Nurhasanah, Nina (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2024)
The development of creative thinking skills in problem-solving is crucial, especially in mathematics at the elementary school level. This study aims to investigate the relationship between the use of Genially learning media and the creative mathematical thinking abilities of fifth-grade students at SDN Sunter Jaya 03 Pagi. Employing a quantitative approach with a correlational design, the study involved all fifth-grade students as the sample. Data were collected through a creative thinking skills test and a questionnaire analyzing the use of Genially. The results indicate that Genially was engaging for students (84%), but they faced language comprehension difficulties (70%). The creative mathematical thinking test revealed that the fluency indicator had the highest percentage (81.5%), while the originality indicator had the lowest (40.5%). Pearson correlation analysis showed no significant relationship between the use of Genially media and students' creative mathematical thinking abilities, with a significance value of 0.731 and a Pearson Correlation of 0.072. These findings suggest that while Genially may be engaging, it does not significantly enhance creative mathematical thinking on its own. The study implies the need for further guidance from teachers in using Genially media to optimize students' creative potential and enhance their understanding of the learning material. This highlights the importance of integrating instructional support with technological tools in the learning process.